Selective Posterior Rhizotomy for the Relief of Spasticity in Cerebral Palsy - W.J. Peacock; Leila J. Arens (South African Journal of Physiotherapy)
Twenty children with increased muscle tone of cerebral origin have been subjected to selective posterior spinal rootlet section. A significant reduction in tone resulting in improvement in motor function was achieved in every case. The first 15 cases are reviewed in detail. The procedure is of value not only in the intelligent ambulant patient but also in the mentally retarded and severely spastic child because handling is facilitated and bladder and bowel control improved. Speech and hand function were improved in a number of patients in whom they had previously been major problems.